SUBCUTANEOUS EMBEDMENT OF THE PERITONEAL DIALYSIS CATHETER BEFORE US (The Moncrief-Popovich Technique) : IS IT STILL USEFULL 25 YEARS LATER ? - Bertrand Morel (RDPLF, 2018)
Abstract : In 1993 , Moncrief and Popovich described an innovative way of implanting a modified peritoneal catheter , by burying subcutaneously the proximal segment , after a classic laparotomy procedure . They thought that, covering the catheter during  the healing phase, would prevent the constitution of an intra-luminal bacterial biofilm, and, therefore, prevent secondary infectious complications, when performing dialysis. If it did not meet the infectious advantage , it appears that this technique of early implantation of the catheter , allows the onset of the treatment with a watertight and painless abdominal wall , with immediately using maximum volumes of dialysate .  We describe the technique as it was adapted to our center and practiced for more than  twenty years , reporting the results of a study in Chambery between 2006 and 2010 . Finally , we discuss the results published in the  literature .